2014
DOI: 10.1111/ina.12151
|View full text |Cite
|
Sign up to set email alerts
|

Test chamber investigation of the volatilization from source materials of brominated flame retardants and their subsequent deposition to indoor dust

Abstract: Brominated flame retardants (BFRs) are ubiquitous in indoor air and dust, leading to human exposure and resultant concerns about their adverse impact on health. Indoor dust has been demonstrated to constitute an important vector of human exposure to BFRs, especially for toddlers. Despite the greater importance of dust contamination in the context of human exposure to BFRs, the mechanisms via which BFRs transfer from source materials to dust have hitherto been subject to only limited research. In this study, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…A detailed explanation of the test chambers is given by Rauert et al (2015). Briefly, stainless steel cylindrical chambers of 10 cm diameter and 20 cm height were used at the University of Birmingham, UK.…”
Section: Test Chambersmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed explanation of the test chambers is given by Rauert et al (2015). Briefly, stainless steel cylindrical chambers of 10 cm diameter and 20 cm height were used at the University of Birmingham, UK.…”
Section: Test Chambersmentioning
confidence: 99%
“…A similar assembly of two PUF disks was attached to the outlet to collect PBDEs in outflow air. Only the 'chamber-side' outlet PUF was treated as a sample as the air-side PUF did not show any breakthrough loss during experimental design development (Rauert et al, 2015). The length of polypropylene tubing attached to the outlet was kept at 2 cm to minimize the loss of PBDEs due to sorption to the tubing surface (Rauert et al, 2015).…”
Section: Test Chambersmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the coarse and fine particles are the main contributor to the deposition (wet and dry) processes of the particle-bounds FRs. However, the major pathways of mass or FRs transfer from treated materials into the dust include different routes: volatilization of FRs from the source products, abrasion of the treated consumer goods and direct contact between dust and materials (Rauert et al, 2015). Several studies have also demonstrated the correlation between concentration of FRs in the air and dust and the FRs sources (Allen et al, 2008;De Wit et al, 2012).…”
Section: Introductionmentioning
confidence: 99%